Kualitas Hidup Orang Tua dengan Anak Disabilitas - Indri Nurasa; Silvia Mareti (Citra Delima : Jurnal Ilmiah STIKES Citra Delima Bangka Belitung, 2022)
Children with disabilities have greater physical and psychological needs than children without disabilities. This will affect the response of parents. The condition of parents in dealing with children with disabilities will also affect the quality of life of parents. Objective: To analyze the quality of life of parents with children with disabilities. Method: Using descriptive quantitative cross sectional approach. The number of samples was 122 respondents using total sampling technique. Results: The domain of quality of life with the highest average value is the domain of social relations (64.80) followed by the domain that has the same value, namely psychological (63.07), and environment (62.98), while the lowest domain is physical health (54.24). The median value of Q1 for the quality of life of the parents in general is 4 which means good, and the median value of Q2 is 4 which means that it is satisfactory.